ANALISIS DAYA SAING BIJI KAKAO INDONESIA DI PASAR DUNIA - NUrtamtomo Hadi Nugroho (University of Jember, 2008)
Indonesia is represents as the producing country of cocoa number three in world. In era of globalization benefit of commerce will only be enjoyed by state having higher competitiveness from other state. This research conducted as a mean to know the 1) trend of growth of Indonesian cocoa seed on year period 1996-2006 and forecasting in year of 2015; 2) specialization of Indonesian cocoa seed on 1996-2006 compared with other producing country 3) ratio of Indonesian cocoa seed acceleration in 1996-2006 compared to with other producing country; 4) make an index to the RCTA of Indonesian cocoa seed in 1996-2006 compared with other producing country 5) the growth of competitiveness of Indonesian cocoa seed in 2015 compared with other producing country. The analyzing methods are using the Arima, ISP, RA, and RCTA. Result of research indicate that the trend of growth of the cocoa production show fluctuate, wide of area, the amount of export and import of the cocoa seed. The forecasting in 2015 shows the same thing. In 1996-2006 Indonesia have specialization as cocoa exporter country. Indonesia competitiveness position in 1999, 2000, 2002, 2003, 2004 is adulthood phase, in the year 1996,1997,1998, 2001, 2005,dan 2006 is exporting phase. Indonesian seed of cocoa have the lower value of ISP compared with Ivory Coast, Ghana, Ecuador, Cameroon, and Nigeria. Ratio of acceleration of Indonesia cocoa seed in 1996-2006 showing compartment of market of seed of cocoa Indonesia can be grabbed by other; dissimilar state. Pursuant to analysis RCTA, Indonesia has competitiveness in commodity of seed cocoa. Assess the RCTA Indonesia still lower compared with Ivory Coast, Ghana, Ecuador, Cameroon, and Nigeria. Forecasting of Indonesian cocoa seed competitiveness in 2015 indicating that Indonesia have specialization as exporter country and at adulthood phase, weak position in market, and have own competitiveness. Indonesian cocoa seed estimated to have the lower value of RA, ISP and RCTA so it just has a little benefit on the global market. Keywords : Cocoa commodity, Competitiveness, Trend, The ISP, RA, RCTA analyses.